Microwave Synthesis, Spectral, Thermal and Electrical Properties of Some Metal Complexes Involving 5-Bromosalicylaldehyde - Rajendra K. Jain; A. P. Mishra; D. K. Mishra; S. K. Gupta (E-Journal of Chemistry)
Microwave-assisted synthesis is a branch of green chemistry. The salient features of microwave approach are shorter reaction times, simple reaction conditions and enhancements in yields. Some new Schiff base complexes of Cr(III), Co(II), Ni(II) and Cu(II) derived from 5-bromosalicylaldehyde with 4-nitro-1,2-phenylenediamine (H2L1) have been synthesized by conventional as well as microwave methods. These compounds have been characterized by elemental analysis, FT-IR, FAB-mass, molar conductance, electronic spectra, ESR, magnetic susceptibility and thermal analysis. The complexes exhibit coordination number 4 or 6. The complexes are coloured and stable in air. Analytical data revealed that all the complexes exhibited 1:1 (metal: ligand) ratio. FAB-mass and thermal data show degradation pattern of the complexes. The thermal behavior of metal complexes shows that the hydrated complexes loses water molecules of hydration in the first step; followed by decomposition of ligand molecules in the subsequent steps. The solid state electrical conductivity of the metal complexes has also been measured. Solid state electrical conductivity studies reflect semiconducting nature of the complexes.